Adventure time. Sugary shorts. Volume two. - Ward, Pendleton, 1982- (KaBoom!, 2016)
"Collecting stories by amazing comic creators from around the world, Sugary Shorts Volume Two stars all your favorite characters from Marceline the Vampire Queen to Cinnamon Bun."--Back cover.